A proposal for the study of perception: around the cognitive semiotics - Silva, Fernando Moreno da (2015)
In five decades of scientific project, the French semiotics follows the path predicted by Hjelmslev (1975, p.132-133), enrolled in the last words of “Prolegômenos ...”: the transition from immanence to transcendence, both governed by immanence. Within its short history, there are three “approaches” in the development of their methodologies: intelligible, sensitive and cognitive. In the intelligible methodology, prevails the formalism of meaning generative trajectory; in the sensitive one, the incorporation of a body that feels; in the cognitive methodology, finally, there is the need to move from a flesh body to a cognitive body, introducing the cognitive activity of the individual in the apprehension of sense. Based on the theoretical tools of French semiotics and taking the nomenclature “cognitive semiotics”, used by some authors as Klinkenberg ( 2000, 2001, 2010), this paper aims to address the problem of perception, continuing with the discussions of sensitive semiotics to understand how the meaning is constructed through the perspective of the cognitive approach. Thus, integrating the intelligible sensitive and cognitive approaches, it is proposed the “perception semiosis scheme” to understand the meaning construction process.